Nichtinvasive Beurteilung aortokoronarer Venenbrücken mit Kernspintomographie - Theissen, P.; Sechtem, U.; Langkamp, Sabine; Jungehülsing, M.; Hilger, H. H.; Schicha, H. (Nuklearmedizin - NuclearMedicine, 1989)
Fortyfour patients with recent cardiac catheterization because of recurrent chest pain after coronary artery bypass surgery were studied by magnetic resonance imaging to evaluate graft patency. To assess the efficacy of this non-invasive method 92 coronary artery bypass grafts were examined by the spin-echo technique. ECG-gated transversal sections were acquired between the diaphragm and the aortic arch. The specificity of magnetic resonance imaging was 83% (48/58) for patent grafts. However, the sensitivity in the detection of occluded bypasses was only 56% (19/34). Despite the good specificity, clinical applications of this method are limited because of its low sensitivity.